Sustainability in Business: Integrating CSR into Long-term Strategy - Wahyuni, Wahyuni; Hidayat, Julia; Ramli, Nur Rizka Amalia; Syam, Sri Ade Nurfatmawati; Salsabilah, Desiyana (Advances in Business & Industrial Marketing Research, 2024)
Purpose: This study investigates the integration of Corporate Social Responsibility (CSR) into long-term business strategies, emphasizing its role in enhancing competitive advantage and sustainability. The research explores how CSR can be embedded into strategic planning, focusing on leadership, organizational culture, and strategic alignment to achieve sustained business success. Research Design and Methodology: The study employs a qualitative systematic literature review approach, analyzing existing literature on CSR integration and strategic management. It synthesizes insights from various empirical studies to develop a comprehensive framework for integrating CSR into business strategies. Findings and Discussion: The findings reveal that effective CSR integration enhances financial and non-financial performance, including customer loyalty, operational efficiency, and market competitiveness. Strong leadership and a supportive organizational culture are critical to embedding CSR into core business strategy. The study identifies key barriers, such as internal resistance and initial investment needs, and drivers, like regulatory pressure and consumer demand, that influence CSR integration. Implications: The study offers practical implications for managers and policymakers, suggesting a strategic approach to CSR that aligns with business objectives. It also provides theoretical contributions by expanding the understanding of CSR's role in achieving long-term sustainability and competitive advantage. Future research should focus on quantitative analysis and the impact of emerging technologies on CSR integration.